Zmienność wzrostu promieniowego czterech proweniencji świerka pospolitego w warunkach środkowej Polski - Klisz, Marcin; Chojnacka-Ożga, Longina; Jastrzębowski, Szymon; Kowalczyk, Jan (Leśne Prace Badawcze, 2016)
The purpose of this study was to determine the growth variability of four provenances of Picea abies on experimental plots in the Wyszków Forest District, central Poland. The experiment was established as a system of random blocks with four repetitions per block. We selected 48 trees from each provenance and the increment cores were colected from sample trees. Standard measurements of the width of annual increments were performed using the WinDendro software. Raw data was then indexed and subject to dendroclimatic analyses based on the average monthly temperatures and precipitation of the period from 1969 to 2012. Furthermore, the COFECHA software was used to check the consistency of the data and to determine the pointer years. High data consistency as well as growth variability of particular provenances in response to climatic conditions were observed. The results obtained here will allow for an improved selection of populations best suited for growing in the climate of central Poland.